Situation Report: Romania, 4 May 1979 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Hungarian Foreign Minister in Romania Western Support for Free Trade Unionists Romanian Media on the Abrogation of the Sino-Soviet Treaty Juanita Kreps Visits Romania New Credits for Romania RCP Cadre Policy and the Exchange of Party Cards Party Structure: A New Tendency to Centralism